2015
DOI: 10.1124/jpet.114.222307
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pachymedusa dacnicolor–Sauvagine Analog as a New High-Affinity Radioligand for Corticotropin-Releasing Factor Receptor Studies

Abstract: The corticotropin-releasing factor (CRF) peptide family comprises the mammalian peptides CRF and the urocortins as well as frog skin sauvagine and fish urophyseal urotensin. Advances in understanding the roles of the CRF ligand family and associated receptors have often relied on radioreceptor assays using labeled CRF ligands. These assays depend on stable, high-affinity CRF analogs that can be labeled, purified, and chemically characterized. Analogs of several of the native peptides have been used in this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The N‐terminus of PD‐Svg shows greater structural relatedness to CRF than PS‐Svg, whereas the C‐terminal sequence of PD‐Svg is similar to PS‐Svg. We found that PD‐Svg is approximately 10 times more potent than PS‐Svg in stimulating cAMP accumulation in cells that express endogenous CRF receptors (Perrin et al, ). Based partly on this, we developed and characterized a radioiodinated analog of PD‐sauvagine, [ 125 I]‐PD‐Svg, which proved to provide advantages over other available radioligands (Perrin et al, ).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…The N‐terminus of PD‐Svg shows greater structural relatedness to CRF than PS‐Svg, whereas the C‐terminal sequence of PD‐Svg is similar to PS‐Svg. We found that PD‐Svg is approximately 10 times more potent than PS‐Svg in stimulating cAMP accumulation in cells that express endogenous CRF receptors (Perrin et al, ). Based partly on this, we developed and characterized a radioiodinated analog of PD‐sauvagine, [ 125 I]‐PD‐Svg, which proved to provide advantages over other available radioligands (Perrin et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…Analogs of PS‐sauvagine (Grigoriadis et al, ) have since become tracers of choice for such studies, offering potential for binding both CRF receptor subtypes with high affinity (Primus et al, ) and localizing them selectively (Lawrence et al, ; Million et al, ; Rominger et al, ). We seized upon the recent isolation of (PD‐) sauvagine from a different frog species, which differed from PS‐Svg in primary structure and showed greater potency in bioassays (Zhou et al, ), to attempt development of a still more useful radioligand (Perrin et al, ). The [ 125 I]‐PD‐Svg tracer employed here binds both CRF receptors with affinities comparable to those of PS‐Svg, but identified consensus sites of expression in greater number and/or sensitivity than its PS‐Svg counterpart, and with lower levels of nonspecific (background) labeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 This new peptide differs substantially from its PS-Svg counterpart in primary structure and was found to be more potent in bioassays. …”
Section: Figurementioning
confidence: 95%